Análisis de la variabilidad de la frecuencia cardiaca durante la imagen mental de caminata (2020)
The study of the autonomic nervous system (ANS) has become relevant due to its response during sports training. Exercise itself improves ans status, but overtraining induces a state of chronic fatigue, unbalancing ANS activity. Therefore, it is necessary to find other methods to improve the sporting performance. The mental image (MI) has been shown as an effective method to improve the performance of certain motor conditions in athletes, exhibiting the activation of the ANS. MI sessions could be used as a training method; thus, the objective of this research was to identify if there is a significative activation of the ANS during and after MI sessions. The heart rate of 15 subjects was monitored during a physical session and during an MI session of a walk in two different speeds. Data was analyzed through ANOVA and it did not show significative changes in the heart rate variability during or after the MI. It’s possible that the result of this research was influenced by the mental effort, the lack of training in MI, and the time used to obtain the data to analyze the heart rate variability.